Dark Noon - Rosendal Nielsen, Thomas (Peripeti, 2023)
Dark Noon premiered in 2019 at Revolverscenen, Teater Republique. Director and script: Ture Biering. Choreographer and co-director: Nhlanhla Mahlangu, Scenography: Johan Kølkjær. Cast: Bongani Bennedict Masango, Joe Young, Lillian Tshabalala, Mandla Gaduka, Siyambonga Alfred Mdubeki, Katlego Kaygee Letsholonyana and Thulani Zwane.